Heterometallic decanuclear [Fe6–Ln4] coordination clusters with enzymatic mimic activity: Synthesis, structures, magnetic properties, and evaluation of catecholase activity. (1st May 2022) - Akhtar, Muhammad Nadeem; AlDamen, Murad A.; Shahid, M.; Ahmad, M. Shahwaz; Khalid, Muhammad; Intisar, Azeem; Khan, Muhammad Usman
Abstract: Three [Fe6 ‐Ln4 ] clusters are isolated through N ‐methyldiethanolamine (H2 mdea) and 3, 5‐dinitrobenzoic acid (Hdnbz) acting as ligands together with sodium azide. The X‐ray study demonstrates that these compounds are isostructural formulated as [Fe6 Ln4 ( μ 4 ‐O)2 ( μ 3 ‐OH)2 (mdea)6 (dnbz)8 (N3 )4 ]·MeCN· a H2 O· b CH2 Cl2 (where Ln = Tb (1 ), a = 2, b = 3; Ho (2 ), a = 2, b = 2; Er (3 ), a = 1, b = 1). All these compounds are centrosymmetric in structure. The catecholase activity for the clusters (1 –3 ) was also studied in methanol by ultraviolet–visible spectrophotometry via 3, 5‐di‐tertiarybutyl catechol (3, 5‐DTBC) employed as a model substrate for the identification of the compounds as a functional model for metalloenzymes. During this study, the parameters for catecholase activity are estimated as K cat = 1022.12 (1 ), 827.76 (2 ), 562.36 (3 ) h −1 ; KM = 0.6858 (1 ), 0.6467 (2 ), 0.4872 (3 ) M; and V max = 0.2840 (1 ), 0.2291 (2 ), 0.1556 (3 ) M min −1 . In the Fe–4 f system, such a type of activity is determined for the first time. The magnetic studies indicate the antiferromagnetic (AF) interactions between the metal centers. Abstract : A series of [Fe6 ‐Ln4 ] (Ln = Tb (1 ), Ho (2 ), Er (3 )) clusters are designed, characterized by single X‐ray crystallography, studied their magnetic properties, and assessed for the catecholase activity.